(De)constructing the City – The “Palimpsest” and Its Use as a Theoretical Model for Urban Research (KULT_online, 2016)
Stadt der Moderne (The Modern City) is an essay collection comprising thirteen different contributions all dealing with cities and metropolises and the representations thereof. The broad definition of the term “city,” the vast temporal and spatial variety of the analysed urban spaces, and the elaborate use of the “urban palimpsest” make Stadt der Moderne a well-informed and multi-faceted contribution to current urban research.